Grammar Teaching and Digital Learning Didactics with Creativity and Gender - Lopes, Ana Sofia; Morgado, Celda (Sensos-e, 2019)
In language teaching, the use of information and communication technologies (ICT) have positive implications, because these are a pedagogical strategy to develop the components of text comprehension and these are a contribution to the grammar teaching. If today technologies are part of children's daily lives, teachers can not ignore the challenges that this digital generation brings, and should make didactic use of ICT. Thus, a didactic sequence was developed in the 3rd grade of the Primary School, in which ICT contributed to linguistic reflection and comprehension around verbal situations and grammatical gender. The goal of the sequence was the construction of a digital book composed of texts about imaginary animals resulting from a mixture of different texts and a script of linguistic comprehension and reflection, in which the students classified the verbal situations expressed by the verbs used in the texts. The students proceeded to assign the sex of the animals originated from the mixture of texts. The data gathered reinforced that the study of verbal situations contributes to the development of reading comprehension, that there is a confusion between grammatical gender and biological sex, and that the use of ICT are a motivational factor in teaching and learning processes. Full Article